Cultural Acculturation on the Mosque Architecture of the Yoni Al-Mubarok Nganjuk - Latif Kusairi; Depy TB Siswanto (Islamic Studies Journal for Social Transformation, 2020)
The aim of this qualitative research was to know the culture acculturation phenomenon on Nganjuk’s Al-Mubarok Mosque architecture. Mosque is a place of worship for Muslim. Yoni Al-Mubarok Mosque which is in the west of Berbek own square, Berbek sub-district Nganjuk Regency, is one of the oldest Mosque in Nganjuk which was built in 19th Century. This mosque was a part of the Afdeeling Berbek existence under Sosrokusumo I (Kanjeng Jimat). Mosque as the place of worship for Muslim does not have an exact rule on its architecture which rise to the distinctiveness of the mosque architecture according to the surrounding culture that influences it. This mosque was influenced by Hinduism and Chinese culture which made this Mosque have different characteristics with other mosques in Nganjuk region.